VOLGOGRAD PLUM VARIETIES AS SOURCE MATERIAL FOR BREEDING TO INCREASE PRODUCTIVITY AND FRUIT SIZE - A. S. Sidnin (Труды по прикладной ботанике, генетике и селекции)
Information is provided on promising plum varieties that are recommended for breeders seeking an increase of productivity and fruit size.